Influenza outbreak management tabletop exercise for congregate living settings - Christina K. Chan; Jerome A. Leis; Heather Candon; Neethu R. Thomas; Jaclyn O'Brien; James Callahan; Brigitte Pascual; Marianna Ofner; Fatima Fazalullasha; Adrienne K. Chan; Jeff E. Powis; Charlie Tan (Cambridge University Press, 2024)
We conducted a tabletop exercise on influenza outbreak preparedness that engaged a large group of congregate living settings (CLS), with improvements in self-reported knowledge and readiness. This proactive approach to responding to communicable disease threats has potential to build infection prevention and control capacity beyond COVID-19 in the CLS sector.